The Effects of Learning Disabilities of a Dyslexic toward Social Relationship in the Movie Like Stars on Earth - Indira Karina Putri; Siti Hafsah; Jepri Jepri (Prologue: Journal on Language and Literature, 2020)
Hermeneutics in this study is a theory that gives an interpretation of meanings and symbolsthat are interpreted as manifestations of a child's social relations with dyslexia. Humansthrough their minds like the ability to have a normal social life like in general with culturalnorms and understandings that he considers correct by using interpretation as a tool forvarious purposes; one of the goals is to communicate with others as a form of adaptation tothe environment. The study has significant value and can be motivated by the daily lives ofchildren with dyslexia which is considered intelligent and normal people in general. Themethod in this study uses a qualitative descriptive research method with hermeneutics byPaul Ricoeur's theory, with two perspectives namely interpretations and symbols. From thisresearch, the researcher found several symbols that must be interpreted so that the meaningcontained in them can be understood, where this movie provides motivation for parents orchildren with dyslexia.